Shielding the Digital Realm with K-Nearest Neighbors in Network Security - Firmansyah, Andri; Sasongko, Ananto Tri (DPPM Universitas Pelita Bangsa, 2023)
Network security is a paramount concern in today's digitally interconnected world. The constant evolution of cyber threats necessitates innovative approaches to safeguarding the digital realm. This paper explores the application of K-Nearest Neighbors (K-NN) in network security, offering a shield against intrusions and vulnerabilities. The research begins with a comprehensive introduction to the escalating landscape of network security challenges, highlighting the critical role of intrusion detection. K-NN, renowned for its pattern recognition capabilities, is a promising solution to fortify network defenses. The methodological journey involves data collection and preprocessing, where relevant datasets are curated and prepared for analysis. Subsequently, a K-NN model is meticulously crafted, focusing on parameter tuning and optimal K-value selection. Metrics, including accuracy, precision, recall, and F1-score, are employed to assess its performance. The findings provide insights into the model's strengths and limitations, offering a valuable perspective on its suitability for real-world network protection. This research demonstrates the potential of K-Nearest Neighbors in shielding the digital realm, reinforcing network security, and exemplifying the efficacy of machine learning in countering evolving cyber threats. It underscores the significance of proactive measures in preserving the integrity and confidentiality of digital assets in an increasingly interconnected world.